Quality of bovine semen diluted and frozen in an extender with sodium caseinate - Pérez, Jackeline (2021)
The aim of this study was to evaluate sodium caseinate (CS) in the dilution and freezing of bovine semen. Fifteen ejaculates from five bulls were diluted and then individually frozen using a diluent composed of tris-glycerol-citric acid with 8% v/v of low-density lipoproteins (LDL) and supplemented with CS in four treatments: CS 3% w/v (CS3), CS 4% w/v (CS4), CS 5% w/v (CS5) and without CS (Control). The mobility and kinetics (SCA® System) and the functional integrity of the membrane (HOS test) of the fresh, extended and thawed semen were evaluated. In addition, the morphology and vitality (eosin-nigrosin) of the fresh and extended semen, and the structural integrity of the membrane (SYBR14/IP), the acrosome integrity (FITC-PNA) and the in vitro fertilizing capacity (IVF) of thawed semen were evaluated. The statistical analysis of the sperm quality parameters was performed using linear models and the comparison of the means by the Tukey test. Statistical analysis of IVF was performed with the Kruskal-Wallis test. CS3 produced an increase in progressive motility and beat cross frequency of thawed semen (p<0.05). CS4 had a deleterious effect on progressive motility of extended semen, while CS4 and CS5 affected the motility, kinetics and membrane integrity of thawed semen (p<0.05). No differences were found for IVF (p>0.05). Supplementation of freezing extender with sodium caseinate can improve post-thaw quality of bovine semen.